QCT/FEA predictions of femoral stiffness are strongly affected by boundary condition modeling. Issue 2 (25th January 2016) - Rossman, Timothy; Kushvaha, Vinod; Dragomir-Daescu, Dan
Abstract : Quantitative computed tomography-based finite element models of proximal femora must be validated with cadaveric experiments before using them to assess fracture risk in osteoporotic patients. During validation, it is essential to carefully assess whether the boundary condition (BC) modeling matches the experimental conditions. This study evaluated proximal femur stiffness results predicted by six different BC methods on a sample of 30 cadaveric femora and compared the predictions with experimental data. The average stiffness varied by 280% among the six BCs. Compared with experimental data, the predictions ranged from overestimating the average stiffness by 65% to underestimating it by 41%. In addition, we found that the BC that distributed the load to the contact surfaces similar to the expected contact mechanics predictions had the best agreement with experimental stiffness. We concluded that BC modeling introduced large variations in proximal femora stiffness predictions.